Can patients with pulmonary hypertension travel to high altitude? - Luks, A. M. (High Altitude Medicine & Biology, 2009)
With the increasing popularity of adventure travel and mountain activities, it is likely that many high altitude travelers will have underlying medical problems and approach clinicians for advice about ensuring a safe sojourn. Patients with underlying pulmonary hypertension are one group who warrants significant concern during high altitude travel, because ambient hypoxia at high altitude will trigger hypoxic pulmonary vasoconstriction and cause further increases in pulmonary artery (PA) pressure, which may worsen hemodynamics and also predispose to acute altitude illness. After addressing basic information about pulmonary hypertension and pulmonary vascular responses to acute hypoxia, this review discusses the evidence supporting an increased risk for high altitude pulmonary edema in these patients, concerns regarding worsening oxygenation and right-heart function, the degree of underlying pulmonary hypertension necessary to increase risk, and the altitude at which such problems may occur. These patients may be able to travel to high altitude, but they require careful pre-trip assessment, including echocardiography and, when feasible, high altitude simulation testing with echocardiography to assess changes in PA pressure and oxygenation under hypoxic conditions. Those with mean PA pressure =35mm Hg or systolic PA pressure =50mm Hg at baseline should avoid travel to >2000m; but if such travel is necessary or strongly desired, they should use supplemental oxygen during the sojourn. Patients with milder degrees of pulmonary hypertension may travel to altitudes <3000m, but should consider prophylactic measures, including pulmonary vasodilators or supplemental oxygen.